Go Near and Join Thyself to This Chariot: African Pneumatic Movements and Transformational Discipleship - Asamoah-Gyadu, J. Kwabena (International review of mission, 2017)
Christian religious innovation has been ongoing in Africa since the early 20th century. It started with indigenous charismatic prophets calling on people to turn over their old deities and submit to the lordship of Jesus Christ. The ministries of these itinerant prophets led to mass conversions culminating in the formation of what became known as the African independent/instituted/initiated churches (AICs). For the best part of the 20th century the AICs defined what counted as Christian in an African indigenous sense. The argument of this article is that the acronym AICs has, since the closing decades of the 20th century, acquired a much broader meaning to include the new Pentecostal/charismatic movements and churches that have burgeoned across the continent. Their trademarks include youthful urban-centred congregations, media-driven ministries, and the preaching of a gospel of prosperity. The contributions of both the classical AICs and the contemporary Pentecostals to African Christianity have been phenomenal. As Christian churches, however, we ought to evaluate them not just in terms of numerical or sociological impact, but most especially in terms of transformational discipleship. There is much to celebrate in transformational discipleship as far as the ministries of these African Reformation movements are concerned, but there as yet remain areas of concern that need to be dealt with for the optimization of Christian impact in Africa.